Given to solve,

`lim_(x->5^(+)) sqrt(25-x^2)/(x-5)`

Removing the negative form the denominator we get

= `- lim_(x->5^(+)) sqrt(25-x^2)/(5-x)`

= `- lim_(x->5^(+)) sqrt(5^2-x^2)/(5-x)`

= `- lim_(x->5^(+)) sqrt((5-x)(5+x))/(5-x)`

= `- lim_(x->5^(+)) sqrt((5+x)/(5-x))`

=`- [(lim_(x->5^(+)) sqrt((5+x))]/ [lim_(x->5^(+)) sqrt(5-x))]`

= `- sqrt(5+lim_(x->5^(+)) x) /sqrt(5-lim_(x->5^(+)) x)`

as `x-> 5^(+)` ,then the denominator tends from 0 to `-1` .

so,

`lim_(x->5^(+)) sqrt(25-x^2)/(x-5)=oo`

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.